Three essays in social economics: social perspectives on international environmental agreements and space tourism - Houston, Mimi, author; Pena, Anita Alves, advisor; Fremstad, Anders, committee member; Bernasek, Alexandra, committee member; Malin, Stephanie, committee member (Colorado State University. Libraries, 2024)
The social realm is an important locus of insight to understand economic behavior. Social economics recognizes that behavior is a "result of complex social interactions with ethical consequences" (ASE, 2023), that not only informs theory, but also broadens the available policy space. Most importantly, it allows for ethical values to enter the study of economics, giving space for considerations such as equity and justice that are inextricably interrelated to economic phenomena and policy outcomes. One area of study where this interdependence is especially pertinent is in the literature exploring country behavior in global environmental negotiations. The transboundary nature of many environmental issues, especially climate change, warrants international cooperation in the form of international environmental agreements (IEAs). In the field of economics, theoretical models of IEA formation (mostly in the for of non-cooperative game theory) suggest that IEAs should be few and far between. However, the post WWII era, especially the last few decades of the 20th Century, have seen a rapid increase in the number of IEAs ratified and entered into force. In the 1990s alone, over 300 IEAs were signed, and since the turn of the twenty-first century, almost 400 new IEAs have been signed. Empirical work has emerged looking to explain why countries sign and ratify IEAs. Chapter 1 expands and contributes to this body of work by taking a closer look at how international ties, in the form of intergovernmental organization membership, formal alliances, and diplomatic exchanges, affect countries' propensity to sign an IEA and by exploring cross- disciplinary theories on the role of socialization in influencing this behavior. Data is compiled from Mitchell's IEA Database along with Correlates of War Project data on the abovementioned international relations metrics. A negative binomial model is fit to a panel of the count of IEA signatures from 151 countries over the years 1960-2005. Results suggest that global relations matter in countries' IEA signature behavior—with intergovernmental organization membership and diplomatic exchanges increasing the number of signatures, while formal (military) alliances have a negative effect. Looking to inform the theoretical side of the economics of IEAs, Chapter 2 takes a feminist epistemological perspective to critique and expand this area of study. Feminist philosophy, namely feminist standpoint epistemology, points to the epistemic effects of social stratification and highlights the influence of Western, masculinist ideals on the economic study of IEAs and the policy space that it informs. It points to the possible role of geopolitical power relations that favor the global North and their economic and environmental ideologies. As a poignant and timely example, the history of the United Nations Framework Convention on Climate Change is used to demonstrate these points. To conclude and move us "toward a feminist foundation of the economics of IEAs," this chapter explores how feminist philosophy and economics offers a more expansive framework to understand country behavior and power relations in this context. Such approaches allow for salient ethical considerations, like equity and justice, that are increasingly recognized as inextricable from environmental policymaking today. The final chapter pivots from the discussion of IEAs toward consideration of expanded worldviews associated with the planet as our environment. This chapter explores a unique set of data from the newly established space tourism market. Specifically, it seeks to learn more about potential positive externalities associated with a changed worldview that astronauts reportedly experience. Using "citizen astronaut" data from nonprofit Space for Humanity's 2019 application round for a sponsored trip to space, this chapter employs a probit model to explore the influence of demographics on the propensity for citizen astronauts to choose environmental aims as their focus for humanitarian work. It is shown that there are complex correlations between region, age, and gender that affect these altruistic aims. The topics explored in this dissertation work together to exemplify the relevance of the social sphere in economics studies. By empirically establishing that global social relations matter (Chapter 1), to exploring how feminist philosophy helps to understand these relationships (Chapter 2), and lastly, by examining prosocial motivations in the space tourism market (Chapter 3), this dissertation represents a key contribution to their respective literatures and to social economics as whole.